2001
DOI: 10.1017/s0022112001003652
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear self-sustained structures and fronts in spatially developing wake flows

Abstract: A family of slowly spatially developing wakes with variable pressure gradient is numerically demonstrated to sustain a synchronized finite-amplitude vortex street tuned at a well-defined frequency. This oscillating state is shown to be described by a steep global mode exhibiting a sharp Dee-Langer-type front at the streamwise station of marginal absolute instability. The front acts as a wavemaker which sends out nonlinear travelling waves in the downstream direction, the global frequency being imposed by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 50 publications
(79 reference statements)
4
96
2
Order By: Relevance
“…This suggests that no stagnation point is associated with the vortex breakdown in this experiment and that a direct transition from columnar to single helical flow occurs. In addition, the predicted frequencies of the m ¼ À1 spiral that can be argued to be selected by the value of x (Pier et al 2001), are seen to be in reasonable qualitative agreement with the frequencies n that could be measured by image analysis, as seen in Table 4.…”
Section: Local Stability Analysissupporting
confidence: 73%
“…This suggests that no stagnation point is associated with the vortex breakdown in this experiment and that a direct transition from columnar to single helical flow occurs. In addition, the predicted frequencies of the m ¼ À1 spiral that can be argued to be selected by the value of x (Pier et al 2001), are seen to be in reasonable qualitative agreement with the frequencies n that could be measured by image analysis, as seen in Table 4.…”
Section: Local Stability Analysissupporting
confidence: 73%
“…It is quite possible that the global mode period is set by conditions at a 'front' located at the upstream edge of the absolutely unstable region of the wake. Such fronts have been shown to exist at least for some classes of spatially developing wakes, and it is the frequency of the dominant mode at the front which determines that of the global mode (Pier & Huerre 2001). This issue remains open and requires further work.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The frequency (and nature) of such global modes can be explored by analysing the complex, nonlinear GinzburgLandau equation as a model of the flow (e.g. Pier et al 1998;Pier & Huerre 2001). Alternatively, it is possible to undertake (usually numerically) a linear stability analysis of full pre-computed solutions of spatially developing flows, to identify their stability and the frequency of any global mode which might result (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that this does not imply that absolute instability is not involved in transition. Pierre and Huerre [23] have shown that when non-linear effects are included a self-sustained non-linear oscillator will always be generated when there is a region of local linear absolute instability. On the rotating disk, Pier [24] has shown that this oscillator will undergo secondary instability close to the absolute instability boundary, providing a possible route to transition.…”
Section: Discussionmentioning
confidence: 99%